Real estate registry. The legal insecurity of the current Peruvian registry system in the optional registration - Sánchez López, Luis Alberto (2016)
In our country and in international law, the Registration Institution has continuously undergone changes both in its regulatory level and in terms of its organization; likewise, in the development of this research work we have tried to approach the Registry Legal Institution with the greatest possible objectivity, in order to try to contribute as much as possible to improve this institution with the present proposal developed. In this way we will also address the treatment given to the subject by scholars and legal specialists not only in our country, but abroad, that is, in comparative law, from where we generally inherit legislative texts many times without investigating their exposition of reasons or in the peculiar circumstances that gave rise to them, being many times transcribed literally. As a premise to the doctrinal treatment we can say that the Peruvian registry system in all cases can be applied correctly when an adequate use is made of the four basic principles that inform the registry: the principle of enforceability, the principle of legitimacy, the principle of public faith and the priority principle. These act as a support for a table, since in the absence of one the entire system loses consistency and the registry does not fulfill the purpose for which it was created, that is, «Serve as a security element» in real estate legal traffic and currently in movable legal traffic, with the Securities Law.